Diversity and seasonality of caddisflies (Insecta: Trichoptera) at Champathong waterfall, northern Thailand - Prommi, Taeng-On; Seetapan, Kriengkrai; Thamsenanupap, Penkhae (Journal of Food Health and Bioenvironmental Science, 2013)
Abstract The adult caddisfly fauna of Champathong waterfall in northern Thailand was sampled monthly using portable black light traps from February to October 2009. All specimens were identified according to species. A total of 762 male individuals were caught, belonging to 72 species of 14 families. The most common species were Chimarra monorum Chantaramongkol and Malicky, 1989, Cheumatopsyche copia Malicky and Chantaramongkol, 1997, and Hydromanicus serubabel Malicky and Chantaramongkol, 1993. Furthermore, the air temperature and precipitation parameters of area data were analyzed. Flight activity is clearly associated with seasonal climatic conditions. Overall Trichoptera species was highest in richness and abundance during February through to April, which coincides with the end of the dry season in the region. Keywords: Light traps; caddisflies; biodiversity; seasonality